(untitled) (Sociologia del diritto, 2023)
Doping is often viewed as a phenomenon limited to some “bad eggs” who decide to break the rules in order to get an undue advantage over their competitors. In this view, doping is represented as the outcome of a single actor’s choice, conceived as isolated from the social context. However, the sociological literature on doping over the last two decades has highlighted that the “bad eggs” metaphor is a simplification, since individual choices should be understood by referring to both the more general influence of the social and cultural contexts and the more specific one of the social networks where athletes are placed. In this article, we present the findings of a qualitative study that integrated an online survey on the (licit and illicit) use of performance-enhancing drugs and supplements by a sample of amateur athletes. This qualitative research aimed at describing athletes’ paths to doping substances use. In particular, we were interested in understanding whether and how doping can amount to a behaviour balancing normality and deviancy. The findings of our research highlight how certain processes shaping our contemporary society (such as medicalization, pharmaceuticalization, emphasis on performance), which macro-sociological analysis refers to in order to explain the development of doping in modern sport, also shape the vocabularies of motives of those who dope, contributing to maintaining doping in a delicate balance between deviance and normality.